Links between protein-source diversity, household behavior, and protein consumption inadequacy in the Indian rural semi-arid tropics - Kumar, Shalander; Pramanik, Soumitra; Reardon, Thomas; Ellanki, Revathi (Frontiers Media, 2025)
Our study analyzes the determinants, sources, and levels of protein consumption among 785 households across nine districts in six Indian states in the semi-arid tropics. We found that 80% of these households consumed less protein than recommended and relied on cereals for 60–75% of their protein intake. Notably, even when protein-rich foods are accessible to households, they still consume them insufficiently. We found that their protein intake deficiency is driven by a lack of diversity of protein sources (in particular, legumes, millets, and livestock), as well as by a dearth of women's education and role in household decision-making and low incomes and assets. We advocate for initiatives to raise nutrition awareness, empower women, and adopt a nutrition-centric farming approach.